Ashwagandha‐induced liver injury: A case series from Iceland and the US Drug‐Induced Liver Injury Network. (11th February 2020) - Björnsson, Helgi K.; Björnsson, Einar S.; Avula, Bharathi; Khan, Ikhlas A.; Jonasson, Jon G.; Ghabril, Marwan; Hayashi, Paul H.; Navarro, Victor
Abstract: Background & Aims: Ashwagandha ( Withania somnifera ) is widely used in Indian Ayurvedic medicine. Several dietary supplements containing ashwagandha are marketed in the US and Europe, but only one case of drug‐induced liver injury (DILI) due to ashwagandha has been published. The aim of this case series was to describe the clinical phenotype of suspected ashwagandha‐induced liver injury. Methods: Five cases of liver injury attributed to ashwagandha‐containing supplements were identified; three were collected in Iceland during 2017‐2018 and two from the Drug‐Induced Liver Injury Network (DILIN) in 2016. Other causes for liver injury were excluded. Causality was assessed using the DILIN structured expert opinion causality approach. Results: Among the five patients, three were males; mean age was 43 years (range 21‐62). All patients developed jaundice and symptoms such as nausea, lethargy, pruritus and abdominal discomfort after a latency of 2‐12 weeks. Liver injury was cholestatic or mixed ( R ratios 1.4‐3.3). Pruritus and hyperbilirubinaemia were prolonged (5‐20 weeks). No patient developed hepatic failure. Liver tests normalized within 1‐5 months in four patients. One patient was lost to follow‐up. One biopsy was performed, showing acute cholestatic hepatitis. Chemical analysis confirmed ashwagandha in available supplements; no other toxic compounds were identified. No patient was taking potentially hepatotoxic prescription medications, although four were consuming additional supplements, and in one case, rhodiola was a possible causative agent along with ashwagandha. Conclusions: These cases illustrate the hepatotoxic potential of ashwagandha. Liver injury is typically cholestatic or mixed with severe jaundice and pruritus, but self‐limited with liver tests normalizing in 1‐5 months.